The consensus of non-linear agents under switching topology using dynamic inversion in the presence of communication noise and delay - Mondal, Sabyasachi; Tsourdos, Antonios (Sage, 2021)
In this study, a consensus protocol for non-linear multi-agent systems using the non-linear dynamic inversion (NDI) technique is presented. It is named as distributed NDI or DNDI. The agents are considered to be working in a randomly changing environment which is realistic. The randomness in the operating environment is introduced by random switching communication topology, delays, and noise. The consensus protocol is obtained as a closed-form expression, which is a critical requirement for real-time implementation. Also, various cases regarding the communication issues have been considered to study the performance of the DNDI controller. The simulation results are found to be satisfactory.
Keywords: communication noise; communication delay; switching topology; non-linear dynamic inversion; multi-agent systems; Consensus